Physicochemical properties of waste palm-based catalysts synthesized from pyrolyzed and hydrothermalized chars for biodiesel production - Rashid, Umer; Hazmi, Balkis; Abdullah, Rose Fadzilah; Ibrahim, Siti Fadhilah; Alsalme, Ali; Tsubota, Toshiki (Springer Science and Business Media LLC, 2022)
Carbon precursor derived from biomass waste gained significant interest as a component of heterogeneous catalysts that can be functionalized with active groups and provides the advantage of separating the catalyst from reactant and products, unlike common homogeneous catalyst. In this study, palm kernel shell (PKS) based char was developed by pyrolysis and hydrothermal carbonization methods and subsequently utilized for synthesizing bifunctional carbon catalyst. The wet impregnation method by loading K2CO3 and CuO provided bi-functional characteristics to the produced chars for conversion into efficient catalysts, which were suitable for concurrent esterification and transesterification processes. The prepared catalysts were characterized by BET, XRD, FESEM, FTIR, TGA, and CO2/NH3 TPD analysis. The report showed that the sample of hydrothermal-assisted carbonization (HTC) treatment possessed higher surface area (4056 m2/g) due to the steady degradation of lignocellulosic composition, thus improving the porous quality of carbon structure compared to normal pyrolytic carbon (2658 m2/g). Additionally, the PKSHAC@K2CO3-CuO catalyst sample embraced more potent acid-basic properties than PKSAC@K2CO3-CuO, yielding 98.4 and 96.7 of FAME respectively, at optimized reaction conditions, the temperature of 65 °C for 3 h, with 15:1 molar ratio of methanol to WCO with 3 wt of catalysts loading.The reusability test showed that PKSHAC@K2CO3-CuO could catalyse up to 80.1 of FAME, while PKSAC@K2CO3-CuO recorded a yield of 60.1. The biodiesel from waste cooking oil was analyzed to meet the ASTM D6751 standard for diesel fuel. The synthesized heterogeneous catalysts using different chars might be widely suitable for low-cost oil feedstocks used for biodiesel production.